Upaya Meningkatkan Aktivitas dan Hasil Belajar PKn Melalui Model Pembelajaran Problem Solving Siswa MTs N 9 Sleman - Hadisurasa (Jurnal Pendidikan Madrasah, 2020)
This research aims to understand the implementation of the problem solving method to improve the motivation and learning outcomes of class IX-A MTs Negeri 9 Sleman, in the 1st semester of the 2017/2018 school year on regional autonomy material. This research is a class action research (Clasroom Action Research) consisting of two cycles covering planning, implementation, observation, reflection. The results showed that the application of methods of learning problem solving can increase the motivation of learning from 9 students or 31.03% in initial study to 17 students or 58.62% in the first cycle and 27 students or 93.10% in the last cycle.